2014
DOI: 10.1192/bjp.204.6.488
|View full text |Cite
|
Sign up to set email alerts
|

Is depression one thing or many?

Abstract: As members of the recent National Institute for Health and Care Excellence (NICE) clinical guideline update for schizophrenia 1 (M.B. and D.S.), we read with interest the excellent meta-analysis of CBT for symptoms of schizophrenia by Jauhar et al. 2 The results are broadly in line with the NICE review and particularly that of Wykes et al, 3 which showed that studies with high methodological rigour, including masking, have a small effect size for positive and total symptoms. Clearly cognitive-behavioural thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
(3 reference statements)
1
7
0
Order By: Relevance
“…SB was also the most common accessory diagnosis. The distribution of these diagnoses is consistent with the general prevalence of mental disorder within the Swiss population [35] and, except for SB, with the literature [8,36,37]. The finding related to SB is also in agreement with its general prevalence in Switzerland, which is higher than most European countries [38][39][40].…”
Section: Discussionsupporting
confidence: 89%
“…SB was also the most common accessory diagnosis. The distribution of these diagnoses is consistent with the general prevalence of mental disorder within the Swiss population [35] and, except for SB, with the literature [8,36,37]. The finding related to SB is also in agreement with its general prevalence in Switzerland, which is higher than most European countries [38][39][40].…”
Section: Discussionsupporting
confidence: 89%
“…4 Although scientists agree in considering that depression is the result of a complex interaction of social, psychological, and biological factors, due to the clinical and etiological heterogeneity it is difficult to clarify its pathophysiology. 5 An increasing body of scientific evidence suggests a relationship between dietary patterns and depression, [6][7][8] and many meta-analyses [9][10][11] have found that adherence to healthy diets is associated with lower risk of depression and less severe depressive symptoms. These findings could be important for the prevention and treatment of depression, but the quality, the precision, and the strength of the evidence need improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Depression can have several negative consequences, being characterized by sad mood and/or loss of interest, affecting thoughts, feelings, behaviors, 2 of 20 physical health and impairing social and occupational functioning [3,4]. Furthermore, over 80% of depressed patients have more than one depressive episode during their lifespan [5,6]. In this context, innovative and effective preventive and therapeutic strategies are required.…”
Section: Introductionmentioning
confidence: 99%